Idle and Active Dresses: Design Briefings from the Wardrobe - Kuzmycz, Alicja; McCorkill, Georgia (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
This paper explores how a wardrobe study, the dress audit, was combined with literature on the dress archetype to create a brief for fashion design practice that aims to increase the active wearing of dresses. Overall, clothing utilisation has declined by over a third in the last 15 years, with dresses being the least worn of any significant item. Unworn dresses amount to hidden wardrobe waste, and increasing their utilisation could reduce fashion overconsumption. A cultural examination of the dress through a lens of sustainability reveals an archetype of the Western fashion system, tied to production and consumption discourses with complex socio-political dimensions. In contrast, the wardrobe study provided vital insights into dress-wearing experiences. Most dresses are now mass-produced, creating a disconnect between designers and wearers, and this paper highlights some of the implications of this divide. The wardrobe study identified three leading factors that impact wearing: fit, occasion, and style. If designers address these three factors alone, it could mitigate up to 80% of low usage issues. These findings helped develop five baseline parameters and create a new brief for fashion design practice that prioritises greater garment utilisation by incorporating the lived experience of wearing within the design process.